Immortality and the existence of God: reformulating the arguments of Plato, Anselm, and Gödel - Apolloni, David (Lexington Books, 2024)
"David Apolloni defends a modern version of Plato's argument for the immortality of the soul and argues the soul is non-physical. The book also defends a version of Gödel's ontological argument for God's existence. Using the results, he supports accounts of the afterlife from those who have had near-death experiences"--